A narrative review of music therapy for neuropsychiatric symptoms in Alzheimer’s disease and rationale for protocolized music teletherapy - Wang, Sonya G.; Cevasco-Trotter, Andrea M.; Silverman, Michael J.; Yuan, Shauna H. (Frontiers in Medicine, 2023)
Introduction Alzheimer’s Disease (AD) constitutes a major societal problem with devastating neuropsychiatric involvement in over 90% of those diagnosed. The large spectrum of AD neuropsychiatric symptoms leads to polypharmacological prescribing that, in turn, poses a major risk for increased side effects. Non-pharmacological interventions such as music therapy (MT) are therefore recommended as first-line treatments. The amalgamation of an aging population, long lifespan, and shortage of qualified music therapists limits access to MT services for AD. Objective The purpose of this paper is to provide a rationale for a protocolized music teletherapy (MTT) intervention to increase accessibility for MT as a psychosocial intervention for neuropsychiatric symptoms in people with AD by conducting a narrative review of the existing MT and AD literature. Methods We conducted a narrative review of MT and MTT publications indexed in PubMed and Google Scholar wherein authors used the Neuropsychiatric Inventory. We examined the impact of MT on neuropsychiatric symptoms of AD and identified MTT as a way to increase access to clinical services. Results MT can have positive impacts on neuropsychiatric symptoms in AD. However, we identified an ensuing need for protocolized MT interventions, access to services, and increased awareness. MTT is an option that can address these needs. Discussion Although MT can have positive effects on neuropsychiatric symptoms and can be beneficial and safe for individuals with AD, the current approach to MT practice is enormously heterogeneous with studies demonstrating variable therapist qualifications, uses of music, therapy approaches, and clinical populations. Congruently, the existing literature indicates that MT has not been standardized with protocolized interventions, making it difficult for clinicians and researchers to objectively assess the evidence, and thus, prescribe MT interventions. The lack of MT standardization, coupled with a low number of music therapists relative to people with AD, result in a lack of awareness that hinders access to MT as a psychosocial treatment for neuropsychiatric symptoms in people with AD. We therefore propose that protocolized MTT interventions are needed to increase access to better address neuropsychiatric symptoms associated with AD.